5 - Social Revolutions - The Preconditions for sustainable Development and People’s Democracies in Africa: A Contribution to the Anyang’ Nyong’o /Mkandawire Debate: by Shadrack B. O. Gutto - Shadrack B. O. Gutto (Africa Development, 1988)
abstract